Laboratory-developed tests in the New European Union 2017/746 Regulation: opportunities and risks - Vogeser, Michael; Brüggemann, Monika; Lennerz, Jochen K.; Stenzinger, Albrecht; Gassner, Ulrich M. (Clinical chemistry, 2022)
In vitro diagnostics (IVD) in the European Union (EU) is facing fundamental change with the implementation of a new regulation termed in vitro diagnostic medical device regulation (IVDR) (1). Going into full effect in May 2022, IVDR will affect 447 million people in 27 countries. There is substantial concern that IVDR will result in over-regulation and potentially result in “the end of the laboratory-developed tests as we know it” (2).In this context, it should be noted that in the USA, the topic of regulation of in-house procedures—and in particular potential regulation of medical practice—has been a subject of controversy for a considerable time and a definitive conclusion is still pending (3-6).